PERILAKU BATANG TEKAN PROFIL BAJA SIKU TUNGGAL PADA STRUKTUR RANGKA BATANG - M. Arief Rahman Panjaitan; Purwandy Hasibuan (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2014)
pplication of axial load on the steel angle can be found at the various structures. One of this structures is bridge and transmission tower. At the application, steel angle which accomodated axial load can be sured having eccentricity. This condition is caused by load position that lies not in center of gravity. But in practice, this eccentricity effect is often ignored and angle steel section is always designed due to axial load. This researsch is carried out to observe steel angle L.30.30.3 behavior that accomodated axial compression load and varied according to their length : 63 cm, 83 cm, 103 cm. In addition, eccentricity effects were also considered as in actual condition. At the first, compression member together with tension member was formed to be truss structure. Experimental work was carried out by giving tension load on the loading plate until compression member achieved its failure. Experimental work results showed that maximum ultimate load capacity